A pesquisa na formação e no trabalho dos professores da educação básica - Kátia Augusta Curado Pinheiro Cordeiro da Silva; Sandra Valéria Limonta (Revista Diálogo Educacional, 2012)
This article presents an analysis of research on teacher's work from elementary public schools in Goiás state and in the Federal District. We use the dialectic and historical materialism as methodological perspective. We bring the discussion of data analysis from a research already completed, conducted in the period from 2007 to 2009, on the research conceptions of elementary school teachers that have a master or a doctor degree. We also present some results from another ongoing research which began in 2010, whose theme is the training for research on the Pedagogy course. The results indicate that teachers with master or doctor degree experience a process of impoverishment of teaching, still wishing to do research, but with no structural conditions to develop them, what makes it necessary to invest in teaching career as a valuation and professionalization policy.